Effects of individually silenced N-glycosylation sites and non-synonymous single-nucleotide polymorphisms on the fusogenic function of human syncytin-2. Issue 1 (3rd March 2016) - Cui, Lina; Wang, Huiying; Lu, Xiaoyin; Wang, Rui; Zheng, Ru; Li, Yue; Yang, Xiaokui; Jia, Wen-Tong; Zhao, Yangyu; Wang, Yongqing; Wang, Haibin; Wang, Yan-Ling; et al.
ABSTRACT: The placental syncytiotrophoblast, which is formed by the fusion of cytotrophoblast cells, is indispensable for the establishment and maintenance of normal pregnancy. The human endogenous retrovirus envelope glycoprotein syncytin-2 is the most important player in mediating trophoblast cell-cell fusion as a fusogen. We constructed expression plasmids of wild-type and 21 single-amino-acid substitution mutants of syncytin-2, including 10 N-glycosylation sites individually silenced by mutagenizing N to Q, 1 naturally occurring single-nucleotide polymorphism (SNP) N118S that introduced an N-glycosylation site, and another 10 non-synonymous SNPs located within important functional domains. We observed that syncytin-2 was highly fusogenic and that the mutants had different capacities in merging 293T cells. Of the 21 mutants, N133Q, N312Q, N443Q, C46R (in the CXXC motif) and R417H (in the heptad repeat region and immunosuppressive domain) lost their fusogenicity, whereas N332Q, N118S, T367M (in the fusion peptide), V483I (in the transmembrane domain) and T522M (in the cytoplasmic domain) enhanced the fusogenic activity. We also proved that N133, N146, N177, N220, N241, N247, N312, N332 and N443 were all glycosylated in 293T cells. A co-immunoprecipitation assay showed compromised interaction between mutants N443Q, C46R, T367M, R417H and the receptor MFSD2A, whereas N118S was associated with more receptors. We also sequenced the coding sequence of syncytin-2 in 125 severe pre-eclamptic patients and 272 normal pregnant Chinese women. Surprisingly, only 1 non-synonymous SNP T522M was found and the frequencies of heterozygous carriers were not significantly different. Taken together, our results suggest that N-glycans at residues 133, 312, 332 and 443 of syncytin-2 are required for optimal fusion induction, and that SNPs C46R, N118S, T367M, R417H, V483I and T522M can alter the fusogenic function of syncytin-2.